'Flipping the script': The not-so-distressed damsel and the shirking of the blame in Curial e Güelfa. - O'BRIEN, ERICA (Scripta, 2019)
This article explores the ways in which motifs of feminine culpability, typically articulated by the male courtly lover to his beloved lady in the Spanish sentimental novel, are subverted in the anonymous fifteenth-century Catalan chivalric novel Curial e Güelfa. This subversion of culpability motifs is facilitated in Curial e Güelfa since there is also a subversion of gender roles within the amorous relationship of the novel's protagonists: a female lover, Güelfa, who courts her male beloved, Curial. I demonstrate how the same tactics used by the male courtly lover in the sentimental novel to blame the beloved lady for his suffering and the demise of the relationship are employed by the female characters of Curial e Güelfa toward the beloved man. However, feminine blame still occurs in Curial e Güelfa, manifested as feminine self-blame and blame between women, while the male characters engage in self-absolution, absolution of other men, and utter shirking of the blame.